(untitled) (Scientific journal of the Fergana State University, 2024)
The article studied the chemical composition of the pulp of three different local grape varieties and one wine variety, and also carried out studies using high-performance liquid chromatography. The moisture level of grape seeds, oil content of seeds, carotenoid content in oil, amount of fatty acids, qualitative and quantitative indicators of saturated and unsaturated fatty acids are presented.